INTEGRATING INTERCULTURAL COMMUNICATION SKILLS INTO THE LANGUAGE CURRICULUM: A LITERATURE REVIEW - Ulfa, Farida; Nurcahyani, Sulis Rizkyka (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
There is an increasing need for cross-cultural communication skills in the era of globalization, where language mastery alone is not enough without cultural understanding. The purpose of this study is to identify effective strategies to incorporate intercultural communication skills in language learning so that students are not only proficient in language but also able to understand and adapt to different cultures. The methods used in this research are literature review and analysis of existing curriculum in several educational institutions. The results show that integrating intercultural communication skills in the language curriculum can improve students' understanding of the cultural context in language use and encourage the creation of a more inclusive and dynamic learning environment. The implications of this study emphasize the need for curriculum adjustments to be more holistic, covering linguistic and cultural aspects, as well as the importance of training for teachers in implementing this approach.